THE MAIN DIRECTIONS OF PSYCHOLOGICAL REHABILITATION OF ONСOGYNEСOLOGIC PATIENTS - L. E. Idrisova; A. G. Solopova; Yu. Yu. Tabakman; A. D. Makatsariya; A. A. Surenkov (IRBIS LLC, 2017)
Psychological rehabilitation of gynecological cancer patients is an important problem of modern medicine. Today, without the qualified psychological help is impossible to imagine the effectiveness of the therapeutic process in oncology. The use of modern methods of diagnosis and treatment has increased the life expectancy of patients. In turn, the use of these technologies have contributed to numerous complications and serious psychosocial disturbances seen in cancer patients. There is a need to change the approach to the recovery of patients by implementing the rehabilitation process of complex psycho programs aimed at the adaptation of the patients to the new conditions of life. The process of psychological rehabilitation it should be viewed as a set of individual and group psychotherapeutic interventions, the main purpose of which is to restore the cancer patient personal and social status, taking into account existing pathologies and restrictions. status, taking into account existing pathologies and restrictions. Thus, the provision of adequate psychotherapeutic assistance on the basis of oncological institutions and rehabilitation centers will improve quality and create favorable living conditions for patients in the community.